Peningkatan Hasil Belajar Matematika Siswa Kelas V dengan Menggunakan Model Inkuiri Terbimbing - Hilyati Zahro; Fitri Handayani, Ucik (JURNAL ARMADA PENDIDIKAN, 2025)
The purpose of this research is to demonstrate an increase in the learning outcomes of fifth grade mathematics students on volume material using the Guided Inquiry learning model. This type of research is classroom action research (PTK). The subjects in this study were 22 fifth grade students from SDN 3 Sungai Besar. Data collection methods using observation, documentation and tests. Data analysis techniques using descriptive qualitative and quantitative. The research data showed that there was an increase in mathematics learning outcomes in students after the action was taken. In Cycle I, the average student learning outcomes were 64 with 27% learning completeness. After using the Guided Inquiry Learning Model in Cycle II, the average student mathematics learning outcome was 71 with 73% learning completeness because there were still students who were not complete. After using the guided inquiry learning model in Cycle III, the average student math learning outcome increased to 81 and all student scores were declared complete, resulting in 100% learning completeness. These results indicate that the guided inquiry model can improve students' math learning outcomes.